OPTIMALISASI PENGELOLAAN REFERENCE DAN MASTER DATA DALAM SISTEM DATABASE - Hafidz Ramadhan Noor Matondang; Muhammad Irwan Padli Nasution (JURNAL ILMIAH EKONOMI DAN MANAJEMEN, 2025)
Reference and master data management is a crucial component in modern information systems and databases, especially in supporting the integrity and efficiency of data processing in various organizational sectors. Problems that often arise, such as data duplication, inconsistency between systems, and lack of management standards, hinder the quality of data-based decision making. This study aims to examine the strategy for optimizing reference and master data management with a focus on a systematic approach through the implementation of Master Data Management (MDM) and data governance policies. The methodology used is a literature study and case study analysis of institutions that have implemented structured data management. The results of the study show that the application of consistent data governance principles, integration of MDM technology, and metadata standardization play a major role in improving data consistency and reliability. The conclusion of this study confirms that optimizing reference and master data management is not only a technical issue, but also strategic and organizational. Keywords: master data, reference data, data management, database, data governance, MDM